2020
DOI: 10.1039/d0fo01418d
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin extract ameliorates dextran sulfate sodium-induced colitis through intestinal barrier improvement, oxidative stress reduction, and inflammatory cytokines and gut microbiota modulation

Abstract: It is widely believed that grape seed proanthocyanidin extract (GSPE) exerts antioxidant and anti-inflammatory effects. Dietary supplementation with GSPE has been reported to alleviate colitis signs in mice, but the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 50 publications
5
46
0
Order By: Relevance
“…Under the naïve condition, Tph1 −/− mice had elevated levels of protective bacteria such as Lachnospiraceae and reduced levels of colitogenic bacteria such as Mucispirillum and Desulfovibrionaceae compared to DKO mice (56,57). Moreover, Dubosiella and Turicibacter that are increased during colitis (58,59) were significantly higher in the more colitic DKO and Atg7 IEC donors and recipients. Furthermore, the transfer of colitic or naïve DKO microbiota to antibiotic-treated mice was associated with increased inflammation severity.…”
Section: Discussionmentioning
confidence: 99%
“…Under the naïve condition, Tph1 −/− mice had elevated levels of protective bacteria such as Lachnospiraceae and reduced levels of colitogenic bacteria such as Mucispirillum and Desulfovibrionaceae compared to DKO mice (56,57). Moreover, Dubosiella and Turicibacter that are increased during colitis (58,59) were significantly higher in the more colitic DKO and Atg7 IEC donors and recipients. Furthermore, the transfer of colitic or naïve DKO microbiota to antibiotic-treated mice was associated with increased inflammation severity.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies demonstrated the beneficial effects of grape compounds and grape by-products in various chronic diseases, including IBD [ 23 , 24 ]. In mice with DSS-induced colitis, grape seed proanthocyanidin extract alleviates colitis symptoms by modulating inflammatory cytokines and oxidative stress, maintaining the intestinal barrier, and by improving the microbial community [ 25 ]. Furthermore, prophylactic consumption of polyphenol-rich grape pomace extracts exerts protective effects against DSS-induced colitis, by decreasing the inflammatory status at the colon level [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore analyzed the microbial distribution. As previously reported, DSS boosted the genera Enterococcus [ 29 ], Turicibacter [ 30 ], Lactobacillus [ 15 ], Dubosiella [ 15 ], and Alloprevotella [ 31 , 32 ], most of which are also considered harmful bacteria in colitis [ 15 , 33 , 34 ]. These results suggested that the main contribution of DSS toward increasing bacterial richness and diversity was harmful bacteria.…”
Section: Discussionmentioning
confidence: 71%
“…Changes in the composition and function of the gut microbiota cause alterations in intestinal ECs and TJ proteins [ 12 , 13 , 14 ], both of which are responsible for controlling gut permeability. An increase in gut permeability is known to facilitate microbial translocation, perpetuating UC [ 15 ]. Therefore, exploiting drugs that synergize gut barrier protection and microbiota regulation could be a promising avenue for UC treatment.…”
Section: Introductionmentioning
confidence: 99%